Coplanar polychlorinated biphenyl-induced CYP1A1 is regulated through caveolae signaling in vascular endothelial cells - Lim, Eun Jin (2008)
Polychlorinated biphenyls (PCBs) are persistent environmental contaminants that can induce inflammatory processes in the vascular endothelium. We hypothesize that the plasma membrane microdomains called caveolae are critical in endothelial activation and toxicity induced by PCBs. Caveolae are particularly abundant in endothelial cells and play a major role in endothelial trafficking and the regulation of signaling pathways associated with the pathology of vascular diseases. We focused on the role of caveolae and their major protein component, caveolin-1 (Cav-1), on aryl hydrocarbon receptor (AhR)-mediated induction of cytochrome P450 1A1 (CYP1A1) by coplanar PCBs. Endothelial cell exposure to PCB77 increased both caveolin-1 and CYP1A1 levels in a time-dependent manner in total cell lysates, with a maximum increase at 6 h. Furthermore, PCB77 accumulated mainly in the caveolae-rich fraction, as determined by gas chromatograph-mass spectrometry. Immunoprecipitation analysis revealed that PCB77 increased AhR binding to caveolin-1. Silencing of caveolin-1 significantly attenuated PCB77-mediated induction of CYP1A1 and oxidative stress. Similar effects were observed in caveolin-1 null mice treated with PCB77. These data suggest that caveolae may play a role in regulating vascular toxicity induced by persistent environmental pollutants such as coplanar PCBs. This may have implications in understanding mechanisms of inflammatory diseases induced by environmental pollutants.